MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA MATERI OPERASI HITUNG BILANGAN BULAT MELALUI METODE DEMONSTRASI DENGAN MEDIA - Risnayati, Cik (Wahana Pendidikan, 2021)
ABSTRACTBased on the results of daily tests of mathematics subjects on the operation of counting integers, it shows the students' low level of mastery of the material. The factor of this is the learning process which is dominated by the teacher, tends to be lecture and the teacher only provides examples of questions. One way to improve students' understanding of concepts is to use demonstration methods with media. The purpose of this study was to improve understanding of the mathematical concept of integer arithmetic operations involving negative numbers in grade VI elementary school students using demonstration methods with media. This research is a classroom action research consisting of two cycles. The subjects of this study were the sixth grade students of SD Negeri 1 Tanjung Raya, totaling 36 students. Data collection techniques, namely by observation and tests. The results showed that the learning outcomes had increased, namely the results of the pre-cycle test 47%, the first cycle 64% and the second cycle to 92%. In addition, the activeness of students in participating in learning activities also increases. Thus it can be concluded that the use of the demonstration method is proven to improve the understanding of the mathematical concepts of the integer arithmetic operation material in students.Key words: integers, demonstration method, conceptual understanding.ABSTRAKBerdasarkan hasil ulangan harian mata pelajaran matematika tentang operasi hitung bilangan bulat menunjukkan rendahnya tingkat penguasaan materi siswa. Faktor terjadinya hal tersebut adalah proses pembelajaran yang didominasi oleh guru, cendrung bersifat ceramah dan guru hanya memberikan contoh-contoh soal. Salah satu cara untuk meningkatkan pemahaman konsep siswa adalah menggunakan metode demonstrasi dengan media. Tujuan penelitian ini adalah untuk meningkatkan pemahaman konsep matematika materi operasi hitung bilangan bulat yang melibatkan bilangan negatif pada siswa SD kelas VI menggunakan metode demonstrasi dengan media. Penelitian ini adalah penelitian tindakan kelas yang terdiri dari dua siklus. Subjek penelitian ini adalah siswa kelas VI SD Negeri 1 Tanjung Raya yang berjumlah 36 orang siswa. Teknik pengumpulan data yaitu dengan observasi dan tes. Hasil penelitian menunjukkan bahwa hasil pembelajaran mengalami peningkatan yaitu hasil tes prasiklus 47%, siklus pertama 64% dan siklus dua menjadi 92%. Selain itu keaktifan siswa dalam mengikuti kegitan belajar juga meningkat. Dengan demikian dapat disimpulkan bahwa penggunaan metode demonstrasi terbukti dapat meningkatkan pemahaman konsep matematika materi operasi hitung bilangan bulatÂ  pada siswa. Kata Kunci : bilangan bulat, metode demonstrasi, pemahaman konsep.